Stereospecific syntheses of 9-(S)-(3-hydroxy-2-phosphonylmethoxypropyl)adenine (HPMPA) - Holý, A; Rosenberg, I (Nucleic acids symposium series, 1987)
9-(S)-(3-Hydroxy-2-phosphonylmethoxypropyl)adenine (HPMPA) was prepared from 9-(S)-(2,3-dihydroxypropyl)adenine (DHPA) via its 3-O-chloromethanephosphonate. The latter compound is obtained by treatment of DHPA with chloromethanephosphonyl dichloride and the 3'-isomer separated from its 2'-congener by ion-exchange chromatography. The 3'-isomer is prepared selectively by the same method starting from 2',6-dibenzoyl derivative of DHPA. The 3'-ester is transformed to HPMPA by treatment with aqueous alkali. Alternatively, 9-(S)-(2-hydroxy-3-triphenylmethoxypropyl)-N6-benzoyladenine can be converted to HPMPA by reaction with dialkyl p-tolylsulfonyloxymethane-phosphonates in the presence of NaH followed by successive acid and alkaline treatment.
Keywords: organofosforové sloučeniny; Adenine; Indicators and Reagents; stereoizomerie; Organophosphorus Compounds; adenin; antivirové látky; Organophosphonates; Antiviral Agents; organofosfonáty; Stereoisomerism; indikátory a reagencie